2019
DOI: 10.1111/ctr.13560
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of polyvalent immunoglobulin use in solid organ transplant recipients: A systematic review and meta‐analysis

Abstract: Polyvalent immunoglobulin is commonly used for desensitization and treatment of antibody‐mediated rejection in kidney transplantation but its impact on other outcomes is not known. This systematic review investigated the impact of immunoglobulin prophylaxis on infection, rejection, graft loss, and death following kidney transplantation. A comprehensive literature search located 18 studies (n = 8 randomized controlled trials). None examined the effect of immunoglobulin prophylaxis in transplant recipients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Such an approach should include immunoguided long‐term antimicrobial prophylaxis, individualized immunization protocols, or the role of IgG replacement therapy in patients with secondary antibody deficiency. A recent systematic review investigated the impact of immunoglobulin prophylaxis on infection after kidney transplantation 35 . None of the studies examined the effect of this intervention in transplant recipients with secondary antibody deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach should include immunoguided long‐term antimicrobial prophylaxis, individualized immunization protocols, or the role of IgG replacement therapy in patients with secondary antibody deficiency. A recent systematic review investigated the impact of immunoglobulin prophylaxis on infection after kidney transplantation 35 . None of the studies examined the effect of this intervention in transplant recipients with secondary antibody deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Important to note that while more data supports a positive relation between hypogammaglobulinemia and infections [19,20], some studies concluded otherwise [21]. Nonetheless, there is still no consensus on preventive measures for infections regarding hypogammaglobulinemia in kidney transplant recipients [21,22,23]. In our case of secondary HGG the decision was made to administer IV IgG in order to correct a substantial deficiency and thus possibly improve patient's outcome.…”
Section: Discussionmentioning
confidence: 88%
“…24,39,282 Data are limited and inconclusive regarding the benefit of IVIG for post-KT SHG. 283 IgG-RT has not been found to provide significant survival benefit in intestinal (including liver) transplant. 278,284 IVIG is also used for non-SHG indications, adding nuance to the decision-making around whether or not to treat post-SOT SHG.…”
Section: Discussionmentioning
confidence: 99%